Electrospun polymeric dressings with tuned collagen type I and antimicrobial peptides activities for enhanced wound healing - Felgueiras, Helena Prado (2017)
[Excerpt] Acute wound therapies target specific phases of wound-healing but do not consider possible disrupts on the usual conduct of each phase (hemostasis, inflammation, proliferation and maturation). Due to a number of potential stimuli, ischemia, bioburden, necrotic tissue, trauma, etc., wounds can stall in one phase of healing, typically inflammation, contributing to the wound chronicity [1]. Chronic wounds are often characterized by a defective matrix and cell debris impair healing, high bacteria counts, prolonged inflammation and moisture imbalance. Conventional therapies identify and remove these barriers to wound-healing by applying individualized treatments [1,2]. Our goal is to engineer polymeric wound dressings by electrospinning for acute to chronic wound care that actively stimulate all phases of healing and prevent bacterial colonization. Our strategy is targetdirected by tuning the activity of different antimicrobial peptides (AMPs) immobilized onto the electrospun polymeric wound dressing (Fig 1). [...]